2013
DOI: 10.1039/c3cp44294b
|View full text |Cite
|
Sign up to set email alerts
|

Buffered chlorogallate(iii) ionic liquids and electrodeposition of gallium films

Abstract: Buffering of Lewis acidic chlorometallate ionic liquids is a useful tool to modify their properties for electrochemical and catalytic applications. Lewis acidic chlorogallate(iii) ionic liquids containing the 1-octyl-3-methylimidazolium cation, buffered with sodium chloride, were studied using (71)Ga NMR spectroscopy and cyclic voltammetry. All the studied Lewis acidic compositions (0.50 < χGaCl3 ≤ 0.75) could be buffered to mild or moderate acidity, but not to neutrality. Electrodeposition of gallium from suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Consequently, the primary benefit of NMR spectroscopy as a speciation tool is the extreme sensitivity of peak shape to changes in speciation, which allows detection of even small amounts of lower-symmetry polynuclear species. 52 More advanced metal NMR studies have been carried out only for chloroaluminate(III) systems. Manipulating the temperature and the pre-acquisition delay time, DE (the time interval between the observe pulse and the onset of data acquisition), Grey and Maciel 45 claimed to have had separated the contributions from [AlCl 4 ] À (narrow peak) and [Al 2 Cl 7 ] À (broad peak).…”
Section: Liquid-state Speciation Studiesmentioning
confidence: 99%
“…Consequently, the primary benefit of NMR spectroscopy as a speciation tool is the extreme sensitivity of peak shape to changes in speciation, which allows detection of even small amounts of lower-symmetry polynuclear species. 52 More advanced metal NMR studies have been carried out only for chloroaluminate(III) systems. Manipulating the temperature and the pre-acquisition delay time, DE (the time interval between the observe pulse and the onset of data acquisition), Grey and Maciel 45 claimed to have had separated the contributions from [AlCl 4 ] À (narrow peak) and [Al 2 Cl 7 ] À (broad peak).…”
Section: Liquid-state Speciation Studiesmentioning
confidence: 99%
“…Seddon et al reported that metallic gallium electrodeposits can be obtained from buffered acidic chlorogallate( iii ) ionic liquids, but not from the corresponding basic and neutral melts. 24 This is due to the formation of the anionic [GaCl 4 ] − complex in the basic and neutral metals and this complex is not electroactive within the electrochemical windows of these metals. Dale et al demonstrated the electrodeposition of gallium, as well as copper–gallium and indium–gallium alloys from the deep-eutectic solvent (DES) Reline, which is a mixture of choline chloride and urea in 1 : 2 molar ratio, as an alternative method to produce CIGS absorber layers for photovoltaic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Beside the Ga-Au surface layer resulting from underpotential deposition (UPD), they also showed that 3-D Ga clusters in the size range from 5-30 nm are formed at the potentials more negative than the UPD. Seddon, K. R. et al [10] reported that buffered chlorogallate (III) ionic liquids can be used to obtain the Ga electrodeposits with improved morphology, compared to that electrodeposited from the unbuffered ionic liquids.…”
Section: Introductionmentioning
confidence: 99%